Hypoxic hepatitis in survivors of cardiac arrest: A systematic review and meta-analysis - Ya-Bei Gao; Jia-Heng Shi; Da-Xing Yu; Hui-Bin Huang (Resuscitation Plus)
Background: Hypoxic hepatitis (HH) is commonly seen in critically ill patients, such as those with cardiac shock, sepsis, and respiratory failure. However, data are limited regarding its impact on the prognosis of patients with cardiac arrest (CA). Methods: We conducted a systematic review and meta-analysis of studies from PubMed, EMBASE, and the Cochrane Library from inception to July 30, 2024. Studies were included if they focused on adult CA patients with HH compared to controls and had a clear definition of HH (defined as a rapid elevation in liver enzyme levels > 20 times the upper limit of normal after CA). The primary outcome was all-cause mortality.Subgroup analyses, sensitivity analyses, and generic inverse variance analyses were conducted. Results: Six studies with 3,005 adults were included. The median prevalence of HH was 16.3 % (ranging from 7.2 to 24.7 %). Overall, patients with HH had a significantly higher risk of all-cause mortality than those without (odds ratio [OR] = 3.49; 95 % CI, 2.19–5.57; P < 0.00001). This finding was confirmed in subgroups, sensitivity analyses, and regression analyses. HH patients were more likely to have a poor neurological outcome (OR = 2.73; 95 % CI, 1.37–5.42; P = 0.004), post-CA shock (OR = 5.77; 95 % CI, 1.76–18.94; P = 0.004), cardiac failure (OR = 35.84; 95 % CI, 6.02–213.31; P < 0.0001), and higher lactate levels (mean difference [MD] = 4.10 mmol/L; 95 % CI, 2.89–5.31; P < 0.00001). In addition, HH required more continuous renal replacement therapy (OR = 4.19; 95 % CI, 3.02–5.82; P < 0.00001), vasopressor therapy, time to return of spontaneous circulation (MD = 5.0 min; 95 % CI, 3.02–6.97; P < 0.00001) but not mechanical ventilation (OR = 1.40; 95 % CI, 1.00–1.97; P = 0.05). Conclusions: Hypoxic hepatitis is not a rare complication after CA, and was independently associated with all-cause mortality. Further prospective, well-designed studies are needed to validate our findings.